Stability of coagulation proteins in lyophilized plasma. (13th December 2014) - Jennings, I.; Kitchen, D. P.; Woods, T. A. L.; Kitchen, S.; Preston, F. E.; Walker, I. D.
Summary Introduction External quality assessment (EQA) is an important component of quality assurance for laboratory tests of haemostasis. Lyophilization of plasma confers stability of labile clotting factors, allowing valid comparison of results between participating centres. However, elevated ambient temperatures in some geographical areas could affect the stability of lyophilized samples in transit. Methods The effect on lyophilized plasma samples of consistent elevated temperature with respect to haemostasis tests was determined in a single centre. The temperature to which packages were exposed during transit was also monitored. Results Survey packages were exposed to average temperatures up to 31.9 °C and maximum temperatures up to 39.7 °C over delivery periods between 1 and 8 weeks. In‐house studies revealed samples to be stable over a 6‐week period at a constant 30 °C, and only small changes were observed for samples exposed to 37 °C for 4 weeks. 6‐week storage at 37 °C was associated with average changes of up to 15% in factor assay activity. Conclusion Lyophilized EQA material employed in UK NEQAS surveys is stable under conditions encountered for the majority of participants, but in cases of delayed delivery of samples, the effect of temperature on sample integrity must be considered when assessing laboratory performance.